Snapshot full Stokes imager by polarization cameras and its application to bio-imaging - Otani, Yukitoshi (SPIE, 2021)
This paper describes a snapshot full- Stokes imager by two polarization cameras with linear micro-polarizer array which is aligned to 0, 45, 90 and 135° of azimuthal direction. A presentation highlights an imager for full Stokes parameters with retarder and two polarization cameras with calibration method for error of retarder to increase an accuracy. We also succeed to analyze a high definition polarization image by Stokes analysis in the Fourier domain although a polarization camera requires 2x2 pixels with linear micro-polarizer array in the space for one polarization analysis. We demonstrate same applications of bio-imaging using a differential interferometric microscope and some industrial applications by high-speed polarization camera.